PERILAKU KELUARGA TERHADAP PENERIMAAN PASIEN SKIZOFRENIA DI WILAYAH KERJA PUSKESMAS BANDA RAYA KOTA BANDA ACEH PEMERINTAH ACEH - , Syamsuri, dr. Carla Raymondalexas Marcira, Sp.JK. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Shizophrenia is very serious mental disorder so that the majority of patients cannot be totally cured and cannot work efectively. The role of the family in accepting schizophrenic patients is greatly needed for the process of healing. Objective: To identify behavior of the family in accepting schizophrenic patients at the working area of Banda Raya Health Center Banda Aceh Municipality. Method: The study used qualitative method with phenomenological approach. Data were obtained through indepth interview